The Spatial Pattern of Fraudulence Risk in Legal Metrology and Its Socio-Economic Drivers: A Case Study Of Bandung, Indonesia - Rifan Ardianto; Yulianti Yulianti (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
This study develops a fraudulence risk in the legal metrology model, gaining insight into urban spatial characteristics as contextual variables that may cause a risk of fraud. The model uses Geographically Weighted Regression on the Metrological Consumer Index data of Bandung, West Java, Indonesia. The findings indicate a wide distribution of recorded fraudulence risk in legal metrology across Bandung, with a spatially clustered pattern based on spatial and context of varying neighbourhood attributes. The results also show an increase in the fraudulence risk in legal metrology in the central business district of Bandung. Such phenomena could be attributed to the residents who trade and are involved in the measurement practice. The findings also suggested that the areas with more senior residents were more likely to have a high fraudulence risk in legal metrology. On the other hand, areas with a high proportion of poor and lesser-educated people exhibit low risk.These findings are helpful for legal metrology authorities seeking to establish appropriate strategies to mitigate adverse impacts of fraudulence risk in legal metrology practice on communities. It can also help identify high fraudulence risk in legal metrology areas to geo-target when and where to disseminate information to increase awareness of the dangers.